Combination of medical and surgical management in successful treatment of caesarean scar pregnancy: a case report series - Anda Pristavu; Angela Vinturache; Elena Mihalceanu; Radu Pintilie; Mircea Onofriescu; Demetra Socolov (BMC, 2020)
Abstract Background There is no clear consensus on the management of caesarean scar pregnancy (CSP), a complex and life-threatening condition. The objective of this study was to present a novel approach to management of CSP that combines medical therapy of multidose methotrexate and mifepristone with active surgical management by uterine curettage and consecutive local haemostasis. Case presentation We report on a prospective case series of six women with first trimester pregnancy, in whom the diagnosis of CSP was confirmed by 2D and color Doppler transvaginal ultrasound and serial hormone chorionic gonadotropin (hCG) testing. Women were between 23 and 36 years old and had at least one previous delivery by caesarean. At admission, gestational age ranged between 6 to 14 weeks, and serum hCG levels between 397 and 23,000 mUI/ml. Upon decision of pregnancy termination, medical management was undertaken in all cases and 1 mg/kg systemic Methotrexate was administered between 1 and 5 daily doses. Mifepristone was part of the treatment in cases with live pregnancy. Surgical management was employed for the cases were an embryo was seen by ultrasound, being prompted by inadequate response to Methotrexate and/or signs of miscarriage with vaginal bleeding. Curettage combined with local isthmic balloon or vaginal pack tamponade prevented further complications. High treatment rates with preservation of fertility was achieved in all patients except one who underwent hysterectomy for invasive placentation. Ultrasound and hCG levels surveillance ensured that the resolution of pregnancy was achieved. Conclusion Women with history of delivery by caesarean section should be carefully monitored in future pregnancies for prompt diagnosis of CSP. Early diagnosis of CSP allows selection of successful conservative therapy. Through this case series we contribute with our experience to the body of knowledge about the management of this serious complication of early pregnancy.